Association of Overweight and Obesity Development Between Pregnancies With Stillbirth and Infant Mortality in a Cohort of Multiparous Women. Issue 3 (March 2020) - Yu, Ya-Hui; Bodnar, Lisa M.; Himes, Katherine P.; Brooks, Maria M.; Naimi, Ashley I.
Abstract : OBJECTIVE: To identify the association of newly developed prepregnancy overweight and obesity with stillbirth and infant mortality. METHODS: We studied subsequent pregnancies of mothers who were normal weight at fertilization of their first identified pregnancy, from a population-based cohort that linked birth registry with death records in Pennsylvania, 2003–2013. Women with newly developed prepregnancy overweight and obesity were defined as those whose body mass index (BMI) before second pregnancy was between 25 and 29.9 or 30 or higher, respectively. Our main outcomes of interest were stillbirth (intrauterine death at 20 weeks of gestation or greater), infant mortality (less than 365 days after birth), neonatal death (less than 28 days after birth) and postneonatal death (29–365 days after birth). Associations of both prepregnancy BMI categories and continuous BMI with each outcome were estimated by nonparametric targeted minimum loss-based estimation and inverse-probability weighted dose–response curves, respectively, adjusting for race–ethnicity, smoking, and other confounders (eg, age, education). RESULTS: A cohort of 212, 889 women were included for infant mortality analysis (192, 941 women for stillbirth analysis). The crude rate of stillbirth and infant mortality in these final analytic cohorts were 3.3 per 1, 000 pregnancies and 2.9 per 1, 000 live births, respectively. Compared with women who stayed at a normal weight in their second pregnancies, those becoming overweight had 1.4 (95% CI 0.6–2.1) excess stillbirths per 1, 000 pregnancies. Those becoming obese had 3.6 (95% CI 1.3–5.9) excess stillbirths per 1, 000 pregnancies and 2.4 (95% CI 0.4–4.4) excess neonatal deaths per 1, 000 live births. There was a dose–response relationship between prepregnancy BMI increases of more than 2 units and increased risk of stillbirth and infant mortality. In addition, BMI increases were associated with higher risks of infant mortality among women with shorter interpregnancy intervals (less than 18 months) compared with longer intervals. CONCLUSION: Transitioning from normal weight to overweight or obese between pregnancies was associated with an increased risk of stillbirth and neonatal mortality. Abstract : Transitioning from normal weight to underweight or overweight between pregnancies was associated with an increased risk of stillbirth; transiting from normal weight to obese was associated with an increased risk of both stillbirth and neonatal death.